SETAPAK: Revealing paths toward communal success through incubation of local heroes - Abimantrana, Lintang Jalu; Katili, Matthew Filbert; Putri, Ravania Alya (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Jatinangor, known for institutions like Universitas Padjadjaran and Institut Teknologi Bandung, faces significant socio-economic disparity. Many underprivileged locals lack access to nearby educational opportunities. This perpetuates inequality and hinders development. The study proposes SETAPAK (Sekolah Terampil Kerja), a program empowering residents through education, mentorship, and leadership training. By linking local resources with innovative solutions, it fosters local leaders for communal success. Recommendations include policies, community engagement strategies, and future research for sustainable impact. Methods: The author expanded on their work using secondary data literature review and innovation based method of solution. Findings: The SETAPAK program focuses on empowering local leaders to address educational inequality and foster sustainable development in Jatinangor by cultivating a growth mindset and providing community-driven solutions. The initiative highlights the transformative potential of education and community empowerment to close socioeconomic gaps and inspire hope for a brighter future. Conclusion: SETAPAK demonstrates a transformative approach to addressing educational inequality and fostering sustainable development by empowering local leaders and cultivating a growth mindset. By bridging gaps in access to education and inspiring community-driven solutions, SETAPAK has the potential to create lasting change in Jatinangor and serve as a model for empowering other regions across Indonesia. Novelty/Originality of this article: This article uniquely highlights a community-driven approach to addressing educational inequality by empowering local leaders and integrating personal narratives to showcase the transformative impact of programs like SETAPAK.